2-[6-(4-Chlorophenyl)imidazo[2,1-b][1,3]thiazol-2-yl]-N′-[(E)-4-methoxybenzylidene]acetohydrazide - Orhan Büyükgüngör; Berin Karaman; Nuray Ulusoy Güzeldemirci; Mehmet Akkurt (Acta Crystallographica Section E, 2011)
In the imidazo[2,1-b][1,3]thiazole group of the title compound, C21H17ClN4O2S, the dihedral angle between the thiazole and imidazole rings is 1.9 (2)°. The mean plane of this group makes dihedral angles of 5.5 (2) and 39.9 (2)° with the benzene rings of the chlorophenyl and methoxyphenyl groups, respectively. The dihedral angle between these two benzene rings is 34.4 (2)°. In the crystal, molecules are connected to each other by intermolecular N—H...O hydrogen bonds along the b axis, generating a C(4) chain. Weak C—H...π interactions also occur.